Prudential regulation of Nigerian banking - Nwankwo, G. O. (Lagos : University of Lagos Press, 1990)
Examines why banks are the most heavily regulated of all industries, the philosophy and methodology and the limits to the regulation. It concludes that regulation can help but the ultimate responsibility for ensuring a sound and healthy banking system rests with the board and management of the institution.
Includes bibliographical references (p. 85-89) and index.
oif 04/03/15
Loan
Keywords: Banks and banking; Banking law; Nigeria